Galectin-9 Mediates the Therapeutic Effect of Mesenchymal Stem Cells on Experimental Endotoxemia - Zhao, Yiming; Yu, Dingding; Wang, Hongda; Jin, Wang; Li, Xiang; Hu, Yonghao; Qin, Yafei; Kong, Dejun; Li, Guangming; Ellen, Acheampong; Wang, Hao (Frontiers in Cell and Developmental Biology, 2022)
Endotoxemia remains a major cause of mortality in the intensive care unit, but the therapeutic strategy is still lacking. Mesenchymal stem cell (MSC) was reported with a tissue-oriented differentiation ability and an excellent immunoregulatory capacity. However, the immunity signaling and mechanisms underlined are not completely understood. In our current study, MSC (2.5×105/ml) was obtained and stimulated with IFN-γ (20ng/ml) for 72 hours. Gal-9 expression on MSC was measured by ELISA, RT-PCR, flow cytometry and immunofluorescence, respectively. Experimental endotoxemia was induced by LPS injection (10mg/kg, i.p.) followed by the treatment with Gal-9 High-expressing MSC, unmodified MSC and Gal-9 Blocking MSC, respectively. Therapeutic effects of MSC were assessed by monitoring murine sepsis score, survival rate, splenocyte proportion rate, inflammatory mediator levels and pathological manifestations. The results showed that Gal-9 expressed in MSC, and this expression was increased in a dose-dependent manner after pre-stimulating with IFN-γ. Adoptive transferring of Gal-9 High-expressing MSC into endotoxemia mice showed relieved symptoms and alleviated organ damage in pathology. Splenocyte analysis indicated that Gal-9 High-expressing MSC could promote macrophage polarization to M2-subtype and boost Treg generation. Moreover, there were also an attenuated pro-inflammatory mediator expressions (TNF-α, IL-1β, IFN-γ and iNOS), and increased anti-inflammatory mediator expressions (T-SOD and IL-35) in the sera and damaged organ homogenates. Additionally, we also found a higher expression of Gal-9 in liver, lung and kidney homogenate. Taken together, this study reveals that the optimized immunoregulatory effect of MSC is mainly mediated by Gal-9 high expression. It provides a novel idea for the investigation of MSC immunomodulatory mechanism and offers a potential strategy for the treatment of endotoxemia in clinical settings.